The Impact of Urban Consolidation on the Planning and Management of Open Space in Western Australia - Bannerman, James (Curtin University, 2021)
There are concerns that increases in dwelling density brought about by urban consolidation might require changes in open space policy to ensure liveability does not deteriorate. A mixed methods approach was adopted utilising semi-structured interviews, spatial analysis and content analysis. It was found that although there were concerns around open space provision there were many other issues that were considered more important The research was carried out through the lens of liveability and governance.